2014
DOI: 10.1007/s10811-014-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of freshwater oleaginous microalgae Desmodesmus sp. NMX451 under nitrogen deficiency and alkaline pH-induced lipid accumulation

Abstract: Many microalgae are reported to accumulate TAG under high concentrations of bicarbonate and nitrogen deficiency, but their physiological responses remain unknown and the associated applied technology is rarely explored. We found that single high concentration of bicarbonate did not enhance lipid content, except when combined with nitrogen limitation in Desmodesmus sp. NMX451, and the lipid contents obtained were independent from nitrogen limitation and alkalinity stress. Further analysis showed that adding bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…2b). The overall increase in TAG under nitrogen deficiency (ÀN) is most likely due to the up expression of de novo FAs biosynthesis, in addition to the conversion of polar lipids (PLs and GLs) into TAG triggered by nitrogen starvation, which has been reported in other green algae (Recht et al, 2014;Xia et al, 2015). A visible increase in relative contents of DAG, MAG and other lipid fractions following an increase of nitrogen supply was also observed.…”
Section: Lipid Composition Related To Culture Conditions and Fatty Asupporting
confidence: 52%
See 1 more Smart Citation
“…2b). The overall increase in TAG under nitrogen deficiency (ÀN) is most likely due to the up expression of de novo FAs biosynthesis, in addition to the conversion of polar lipids (PLs and GLs) into TAG triggered by nitrogen starvation, which has been reported in other green algae (Recht et al, 2014;Xia et al, 2015). A visible increase in relative contents of DAG, MAG and other lipid fractions following an increase of nitrogen supply was also observed.…”
Section: Lipid Composition Related To Culture Conditions and Fatty Asupporting
confidence: 52%
“…3d, the volumetric content of chlorophyll firstly increased and then began to decease linearly from day 5 and day 8 with ÀN and +0.5N supplements, respectively. The decline of chlorophyll content is a general response to nitrogen deficiency in green algae (Xia et al, 2015;Ikaran et al, 2015), since nitrogen is a major element in chlorophyll molecules and unavailable of this nutrient could prevent chlorophyll synthesis. Due to the combined effects of carotenoids accumulation and chlorophyll degradation, the Car/Chl ratio therefore increased much faster at high light than that at low light.…”
Section: Lipid Composition Related To Culture Conditions and Fatty Amentioning
confidence: 99%
“…Scenedesmus Meyen is a freshwater and marine genus with 433 known species worldwide 17 , of which 27 species has been reported in aquatic ecosystems of Iran 18 . In nature, the cytoplasmic oil droplets are accumulated under stressful environmental conditions, such as high temperature, light intensity and rise in salinity [19][20][21][22] . In culture, nutritional composition of the medium has more effects on the total lipid content and fatty acid profile, among which nitrogen, silicon and phosphorus have greater roles [20][21][22][23][24] , followed by iron [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…In nature, the cytoplasmic oil droplets are accumulated under stressful environmental conditions, such as high temperature, light intensity and rise in salinity [19][20][21][22] . In culture, nutritional composition of the medium has more effects on the total lipid content and fatty acid profile, among which nitrogen, silicon and phosphorus have greater roles [20][21][22][23][24] , followed by iron [25][26][27][28] . In 1987, the lipid content and fatty acid composition of Scenedesmus obliquus was determined 29 , but at a later time, the values differed within the species [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that the lipid content in microalgae can accumulatively increase under conditions of combined nitrogen deficiency with high light (Ho et al 2012;Münkel et al 2013), or with high salt (Su et al 2010;Feng et al 2014), or at high pH (Gardner et al 2010;Mus et al 2013;Xia et al 2014b). Furthermore, starch degradation is more or less responsible for inducing lipid accumulation under above combined conditions.…”
Section: Introductionmentioning
confidence: 99%